Diagnosis Penyakit Tanaman Melon Menggunakan Metode PROMETHEE - Dito Rizki Pramudeka; Nurul Hidayat; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Cultivation of melon plants requires optimal care and appropriate environmental conditions, as they are susceptible to pest and disease infections. This leads to crop failure due to errors from the handling and selection of the pesticides used in tackling them. The agricultural extensions at this time are still have some difficulty to identify the diseases that attacked the melon plants despite the clear differences between each melon plants and determine the solutions for handling and to eradicate the disease. Based on the said problems, a melon plants' diseases diagnosing system is designed. The Promethee method can be used as a decision-assisting method by comparing the symptoms of one disease with another using the criteria of preference. In the melon plants' diseases diagnosing system using Promethee method's main functions are calculating the value of paired comparison deviation for each disease and calculate the value of stream flow in the form of Entering Flow, Leaving Flow, and Net Flow. The melon plants' diseases diagnosing system using 30 test data resulted in an accuracy rate of 86.67% by using Usual and Gaussian preference criteria. The difference in the level of accuracy in each type of preference is determined by the weight of each symptom from each disease as well as the indifference threshold and the preference threshold used in the calculation.